A Person-Centered Therapy Approach in Counseling for Early Childhood Children Experiencing Separation Anxiety at School - Ansori, Rahmat; Komsi, Dwi Noviana; Mabruria, Arni (Journal of Childhood Development, 2025)
This study aims to describe the application of the Person-Centered Therapy (PCT) approach in counseling to help early childhood children experiencing separation anxiety while attending school in Lubuk Linggau City. Separation anxiety arises when children feel afraid and insecure when separated from their parents, characterized by crying, refusal to go to school, and a desire for parents to accompany them. This study used a qualitative approach with a case study method through observation, interviews, and documentation of children, teachers, parents, and school counselors. The results showed that the application of PCT, which emphasizes empathy, unconditional acceptance, and authenticity of the counselor, can create a safe and comfortable counseling atmosphere for children. Through this process, children learn to recognize, express, and manage their feelings better. This approach is effective in reducing separation anxiety, increasing self-confidence, and helping children adapt to the school environment. The success of this approach lies not only in the counseling technique, but also in the quality of the empathetic relationship between the counselor, child, teacher, and parent. With the support of an accepting environment, children can develop a sense of security, self-confidence, and readiness to adapt to the school environment.